2011
DOI: 10.1177/1941738111410378
|View full text |Cite
|
Sign up to set email alerts
|

A Treatment-Based Classification Approach to Examination and Intervention of Lumbar Disorders

Abstract: Context:Low back injuries are a common occurrence in athletes and often result in missed competition and practice time. The examination of athletes with low back pain commonly involves diagnostic imaging, which rarely guides the clinician in selecting the appropriate interventions.Data Acquisition:All years of PubMed, CINAHL, PEDro, and SPORTDiscus were searched in December 2010. Keywords included treatment based classification and lumbar with the following terms: rehabilitation, treatment, athlete, low back p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 77 publications
(163 reference statements)
0
6
0
Order By: Relevance
“…19 A change in the ODI score in our study was found to be 5.84 points which falls in the range of minimum detectable change (MDC) of 4–10 points in the literature. 28 The minimal clinically important difference (MCID) values for RMDQ depend on the initial score of the patients. The MCID values are calculated in five subgroups i.e., 0 to 8 (MCID = 2), 5 to 12 (MCID = 4), 9 to 16 (MCID = 5), 13 to 20 (MCID = 8) and 17 to 24 (MCID = 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 A change in the ODI score in our study was found to be 5.84 points which falls in the range of minimum detectable change (MDC) of 4–10 points in the literature. 28 The minimal clinically important difference (MCID) values for RMDQ depend on the initial score of the patients. The MCID values are calculated in five subgroups i.e., 0 to 8 (MCID = 2), 5 to 12 (MCID = 4), 9 to 16 (MCID = 5), 13 to 20 (MCID = 8) and 17 to 24 (MCID = 8).…”
Section: Discussionmentioning
confidence: 99%
“…20 These criteria were a symptom duration of 6 weeks, age between 18 and 65 years, initial Oswestry disability index (ODI) score of 20–60% since a majority of patients with acute LBP have been found to have an initial ODI score within this range. Other inclusion criteria such as unilateral symptoms proximal to the knee and no bilateral symptoms were set based on treatment-based classification criteria 28 since it provides an evidenced-based framework in the appropriate conservative management of individuals with LBP. The final inclusion criterion was confirmed lumbar dysfunction based on MET structured diagnostic protocol.…”
Section: Methodsmentioning
confidence: 99%
“…To enable both torque application to one innominate and fixation of the opposite innominate, a rigid metal plate was screwed to each innominate through the compact bone at the height of the iliac crest, above the acetabulum and through the ischial tuberosity. One plate was attached to the frame to fix the bone, while the second was connected to a steel bar and axle to allow application of an incremental force A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 7 resulting in a moment in the sagittal plane. To allow three-dimensional movements of the innominate on the non-fixed side and the sacrum, the axle was equipped with two universal joints and one prismatic sliding joint (Fig.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The patients referred for physiotherapy were classified into various subgroups: direction‐specific exercises (Group 2), manipulation (Group 3), stabilization exercises (Group 4), and traction (Group 5) (Table ). The criteria for allocating the patients into appropriate TBC groups along with the operational definitions of physical tests to be performed are described in detail in other works (Apeldoorn et al, ; Burns et al, ; Fritz et al, ; Hebert, Koppenhaver, & Walker, ). All patients were provided with therapy thrice a week for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%